2022
DOI: 10.1097/mao.0000000000003651
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Volumetric Tumor Regression During Wait-and-Scan Management of 952 Sporadic Vestibular Schwannomas

Abstract: ObjectiveSpontaneous tumor shrinkage during wait-and-scan management of sporadic vestibular schwannoma is generally considered an uncommon phenomenon. However, most data informing this understanding stem from single-slice linear tumor measurements taken in the axial imaging plane. The objective of the current work was to characterize the regression capacity of sporadic vestibular schwannomas using volumetric tumor measurements.Study DesignRetrospective cohort study using slice-by-slice, three-dimensional volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…[ 1 , 2 , 5 , 12 , 13 , 16 , 21 ] Recent studies have shown that 123 of 952 cases demonstrated tumor shrinkage during a median observation period of 1.2 years, suggesting that natural shrinkage may occur more frequently than previously thought. [ 10 ] However, the cause of this natural regression remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 , 2 , 5 , 12 , 13 , 16 , 21 ] Recent studies have shown that 123 of 952 cases demonstrated tumor shrinkage during a median observation period of 1.2 years, suggesting that natural shrinkage may occur more frequently than previously thought. [ 10 ] However, the cause of this natural regression remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Institutional review board approval was obtained from each participating center before data collection (institutional review board numbers 15-008224, 112016-040, and S13-00063, respectively). Although the present analysis is unique, the patient data presented in the current publication overlap with previously published work (16,17). A full description of the methodology used in the current work can be found elsewhere (17), but briefly, slice-by-slice volumetric tumor measurements were performed on consecutive MRI scans for each patient undergoing wait-and-scan management at each participating center.…”
Section: Clinical Datamentioning
confidence: 99%
“…By contrast, a 2016 systematic review that compiled data from many studies of VS growth behavior found that 50.1% of followed tumors demonstrated growth at 5 years (4). Numerous studies have identified a lower rate of growth for small tumors compared with larger tumors (5). This implies that reviews encompassing all tumor sizes may overestimate the growth for small tumors.…”
mentioning
confidence: 99%